Is rectal douching and sharing douching equipment associated with anorectal chlamydia and gonorrhoea? A cross-sectional study among men who have sex with men. (20th January 2017) - Achterbergh, RCA; van der Helm, JJ; van den Boom, W; Heijman, T; Stolte, IG; van Rooijen, MS; de Vries, HJC
Abstract : Introduction: Men who have sex with men (MSM) are at high risk for anorectal chlamydia and gonorrhoea infections. Many MSM use rectal douches in preparation for sex, which might break down the mucosal barrier function and facilitate the acquisition of STI. We determined whether rectal douching or sharing douching equipment was associated with anorectal chlamydia and gonorrhoea. Methods: In a cross-sectional study among 994 MSM attending the STI outpatient clinic of Amsterdam between February and April 2011, data were collected on rectal douching, sexual behaviour and STI. We used multivariable logistic regression analysis to determine the association between rectal douching, including sharing of douching equipment, and anorectal chlamydia and gonorrhoea for those reporting receptive anal sex. We adjusted for other risk behaviour, that is, condom use, number of partners and HIV status. Results: Of 994 MSM, 46% (n=460) practised rectal douching, of whom 25% (n=117) shared douching equipment. Median age was 39 years (IQR 30–47), median number of sex partners in the 6 months prior to consult was five (IQR 3–10) and 289 (29.0%) participants were HIV positive. The prevalence of anorectal chlamydia and/or gonorrhoea for those reporting receptive anal sex was 9.6% (n=96). In multivariable analysis, HIV positivity (aOR=2.2, 95% CI 1.3 to 3.6), younger age (aOR=2.5, CI 1.4 to 4.5 for those aged <35 years compared with those aged ≥45 years), and more sexual partners (aOR=1.2, 95% CI 1.0 to 1.5 for 1 log increase) were significantly associated with anorectal STI. However, rectal douching or sharing douching equipment were not significantly associated with anorectal chlamydia and/or gonorrhoea (p=0.647). Conclusions: Almost half of MSM used rectal douching and a quarter of these shared douching equipment. Though using douching equipment does not appear to contribute to anorectal chlamydia and gonorrhoea in this study, STI prevalence remains high and prevention strategies like early testing and treatment remain of utmost importance.